A modified medium for improved sporulation of gray mold pathogen, Botryotinia ricini (Godfrey) Whetzel in castor (Ricinus communis L.): A MODIFIED MEDIUM FOR IMPROVED SPORULATION OF GRAY MOLD PATHOGEN IN CASTOR - R D PRASAD,; R BHUVANESWARI, (Journal of Oilseeds Research, 2014)
Oat meal agar medium enriched with gallic acid, L-asparagine and castor pericarp extract was developed to enhance sporulation of castor gray mold pathogen, Botryotinia ricini. The enriched oat meal agar medium supported higher sporulation compared to oat meal agar medium and corn meal agar medium which are commonly used for growing B. ricini.